A strain‐specific multiplex RT‐PCR for Australian rabbit haemorrhagic disease viruses uncovers a new recombinant virus variant in rabbits and hares. Issue 2 (10th December 2017) - Hall, R. N.; Mahar, J. E.; Read, A. J.; Mourant, R.; Piper, M.; Huang, N.; Strive, T.
Summary: Rabbit haemorrhagic disease virus (RHDV, or GI.1) is a calicivirus in the genus Lagovirus that has been widely utilized in Australia as a biological control agent for the management of overabundant wild European rabbit ( Oryctolagus cuniculus ) populations since 1996. Recently, two exotic incursions of pathogenic lagoviruses have been reported in Australia; GI.1a‐Aus, previously called RHDVa‐Aus, is a GI.1a virus detected in January 2014, and the novel lagovirus GI.2 (previously known as RHDV2). Furthermore, an additional GI.1a strain, GI.1a‐K5 (also known as 08Q712), was released nationwide in March 2017 as a supplementary tool for wild rabbit management. To discriminate between these lagoviruses, a highly sensitive strain‐specific multiplex RT‐PCR assay was developed, which allows fast, cost‐effective and sensitive detection of the four pathogenic lagoviruses currently known to be circulating in Australia. In addition, we developed a universal RT‐qPCR assay to be used in conjunction with the multiplex assay that broadly detects all four viruses and facilitates quantification of viral RNA load in samples. These assays enable rapid detection, identification and quantification of pathogenic lagoviruses in the Australian context. Using these assays, a novel recombinant lagovirus was detected in rabbit tissue samples, which contained the non‐structural genes of GI.1a‐Aus and the structural genes of GI.2. This variant was also recovered from the liver of a European brown hare ( Lepus europaeus ). The impact of this novel recombinant on Australian wild lagomorph populations and its competitiveness in relation to circulating field strains, particularly GI.2, requires further studies.